Systems Thinking in an era of climate change: Does cognitive neuroscience hold the key to improving environmental decision making? A perspective on Climate-Smart Agriculture - Lalani, Baqir; Gray, Steven; Mitra-Ganguli, Tora (Frontiers in Integrative Neuroscience, 2023)
Systems Thinking (ST) can be defined as a mental construct that recognises patterns and connections in a particular complex system to make the “best decision” possible In the field of sustainable agriculture and climate change, higher degrees of ST are assumed to be associated with more successful adaptation strategies under changing conditions, and “better” environmental decision making in a number of environmental and cultural settings. Future climate change scenarios highlight the negative effects on agricultural productivity worldwide, particularly in low-income countries (LICs) situated in the Global South. Alongside this, current measures of ST are limited by their reliance on recall, and prone to possible measurement errors. Using Climate-Smart Agriculture (CSA) practices (CSA), as an example case study, in this paper we explore: (i) ST from a social science perspective; (ii) cognitive neuroscience tools that could be used to explore ST abilities in the context of LICs; iii) an exploration of the possible correlates of systems thinking: observational learning, prospective thinking/memory and the theory of planned behaviour and (iv) a proposed theory of change highlighting the integration of social science frameworks and a cognitive neuroscience perspective. We find, recent advancements in the field of cognitive neuroscience provide exciting potential to explore previously hidden forms of cognition related to ST especially in a low-income country/field setting; improving our understanding of farmers indigenous knowledge, environmental decision-making and increasing ethnic representation. Finally, our proposed interdisciplinary approach can be used as a starting point to encourage discussion and guide future research in this space.